EXPLORING THE CONTEXTUAL IMPLICATIONS OF KOFI ABREFA BUSIA’S SOCIO-POLITICAL ETHICS FOR CONTEMPORARY GHANA - Isaac Boaheng (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Christian presence in Ghana is enormous in the 21st century. With 71.2 percent of Ghanaians professing Christianity, one would expect Ghanaian public life to depend immensely on Christian norms. However, the secularization and privatization of Christianity has resulted in the marginalization of the prophetic voice of believers in the Ghanaian public arena. The need for a theological response to Ghana’s socio-political context is an urgent concern. In response, this article reflects on how the socio-political thoughts of Kofi Abrefa Busia may be applied to contemporary Ghanaian socio-political discourses to address the country’s socio-political needs. The paper is a literature research that critically examines materials extracted from major publications by Busia and other scholars. The study concludes that the solution to Ghana’s socio-political challenges depends on the collective efforts of all citizens regardless of political, ethnic or religious affiliation.